PENINGKATAN KAPASITAS PEMASARAN UMKM DESA RAJABASA LAMA I MELALUI PELATIHAN DAN PENDAMPINGAN E COMMERCE - Korinatul Muslimah; Maisaroh; Dewi Puspita Sari (JOURNAL OF COMMUNITY DEDICATION, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of the village economy, including in Rajabasa Lama I Village, Labuhan Ratu District, East Lampung Regency, which offers a variety of superior products such as banana chips, ground coffee, and traditional foods. Despite their broad market potential, most MSMEs still rely on conventional marketing, limiting their market reach. Challenges include a lack of digital technology knowledge, promotional content creation skills, and online marketing strategies. The Community Service Program through Real Work Lectures (KKN) was implemented for 25 days (July 8–August 2, 2025) with the aim of increasing the marketing capacity of MSMEs through e-commerce and social media training and mentoring. Implementation methods included observation, planning, preparation, training, mentoring, and evaluation. The materials provided included an introduction to e-commerce, social media utilization, marketplace account creation (Shopee, Tokopedia), product photography techniques, and digital promotion strategies. The results of the activity showed that 100% of participants successfully created marketplace accounts, 70% were able to upload products independently, and some reported increased interaction with potential buyers on social media. Participants provided positive feedback and recommended further training in creative content creation and support for promotional tools. This activity demonstrated that implementing e-commerce can expand marketing reach, increase interaction with potential buyers, and open up broader market opportunities.